2017
DOI: 10.1097/psy.0000000000000474
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Neurocognition in Older Adults With Cardiovascular Risk Factors and Cognitive Impairment

Abstract: Objective To determine the relationship of lifestyle factors and neurocognitive functioning in older adults with vascular risk factors and cognitive impairment, without dementia (CIND). Methods One hundred sixty adults (Mean = 65.4±6.8 years) with CIND completed neurocognitive assessments of executive function, processing speed, and memory. Objective measures of physical activity using accelerometry, aerobic capacity determined by exercise testing, and dietary habits quantified by the Food Frequency Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…Additional mobility performance metrics, including cumulated posture duration and postural-transition, could increase the AUC from 0.78 to 0.93 for detection of cognitive-impaired cases. Previous studies investigating association between mobility performance and cognitive impairment showed that activity level and daily steps are positively associated with cognitive function in older adults [19][20][21][22][23][24]. Results of this study are in line with the previous studies.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Additional mobility performance metrics, including cumulated posture duration and postural-transition, could increase the AUC from 0.78 to 0.93 for detection of cognitive-impaired cases. Previous studies investigating association between mobility performance and cognitive impairment showed that activity level and daily steps are positively associated with cognitive function in older adults [19][20][21][22][23][24]. Results of this study are in line with the previous studies.…”
Section: Plos Onesupporting
confidence: 92%
“…Previous studies have demonstrated that in older adults, people with cognitive impairment exhibit lower level of activity [19][20][21]. However, in previous studies, the assessment of mobility performance mainly relied on self-reported questionnaires [19][20][21], Actigraphy [22,23], or accelerometerderived step count [24]. Although self-reported questionnaire is easy to access without the need of any equipment or device, its main limitation is lacking of objectivity [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study DSI has been validated in a populationbased setting to predict late-life dementia (Pekkala et al, 2017). Identification of persons at risk for global cognitive decline may aid in early detection of persons at risk of dementia and may help to develop therapeutic or preventive measures to postpone or even prevent further cognitive decline and dementia (Blumenthal et al, 2017). This is especially important since previous research has shown that preventive interventions for dementia were more effective in persons at risk than in unselected populations (Moll van Charante et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary patterns have also gained interest, as a growing number of prospective studies have demonstrated that better adherence to dietary patterns with higher intake of fruits, vegetables, whole grains, and reduced intake of saturated fat and complex carbohydrates appear to be associated with reduced ADRD risk [137][138][139][140][141]. For example, greater adherence to the DASH diet, [142][143][144][145][146][147] MeDi, and MIND [148][149][150] have all been associated with lower ADRD risk. However, there have also been null findings, with recent systematic reviews reporting that evidence linking dietary patterns to ADRD outcomes remains inconclusive [113,151,152].…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Although individual lifestyle components appear to confer lower ADRD risk, preliminary evidence suggests additive benefits associated with each component, such that individuals engaging in regular exercise and healthier diets show the lowest risk [203][204][205]. Data from the WHICAP project demonstrated that participants engaging in physical activity or the MeDi diet had lower risk of Alzheimer's Disease (AD), and participants engaged in both had the lowest prospective risk of AD [206].…”
Section: Randomized Trials Combining Exercise and Dietary Modificationmentioning
confidence: 99%